A Fuzzy Logic Based Power Management System for a Hybrid Microgrid - Md. Shamsul Arifin (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2021)
A fuzzy logic-based power management system for a hybrid microgrid is designed in this paper. This designed system is capable to manage the generations considering the load conditions. Consequently, a balance is maintained between generations and load. Furthermore, the system is capable to monitor and manage the storage system charging and discharging as well as to support the external load by sharing power as per considering the situation. Moreover, to make this system more efficient it is such designed that, the storage system will not take any energy from the conventional generation units of the microgrid. Additionally, it is also ensured that, no power will be delivered to the external load utilizing storage or generator. The “Fuzzy Logic Designer” toolbox of MATLAB is used to observe the relationship between the input and output variables, after establishing the fuzzy sets and rules. Furthermore, transferring the fuzzy data sets and rules to MATLAB Simulink and performing different case studies, the effectiveness of the designed system is verified numerically.